Model Regresi Linier Berganda Dalam Menganalisis Faktor-Faktor Urbanisasi Di Jawa Timur - Octavia Putri Anggraini; Nurissaidah Ulinnuha; Moh Hafiyusholeh (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
Urbanization occurs when population increases rapidly, encouraging individuals to migrate from villages to big cities. This phenomenon is triggered by the availability of wider employment opportunities and easier access to resources and technology. However, urbanization also has several negative impacts on the environment, such as reducing the ability to create a comfortable and healthy environment for city residents. This study aims to analyze the factors that influence urbanization in East Java Province using multiple linear regression. The data used is quantitative and was obtained from the East Java Provincial Statistics Agency in 2024. The variables analyzed include poverty levels, security levels, health, education, and unemployment rates. The partial analysis results indicate that the Education Ratio variable has a significant influence on urbanization in East Java, with a coefficient of determination value of 54.1%. These findings are expected to contribute to the formulation of more targeted development policies in managing the pace of urbanization.